Behind the Scenes of Learning: How Administration Drives Education - Sarifudin, Sarifudin; Utami, Sekar; Nasrudin, Amrullah (JURNAL AL-TANZIM, 2025)
This study aims to analyze the leadership strategies employed by the Head of Administration in enhancing the quality of administrative services in schools. The method used is a descriptive, qualitative approach through interviews, observation, and documentation, with triangulation techniques employed to ensure data validity. The results show that the strategies implemented include the preparation of competency-based job descriptions, selective staff training, the provision of performance-based incentives, and regular evaluation of administrative performance. Supporting factors include staff professionalism, the availability of infrastructure, and operational funding support. However, service quality is still hampered by low staff discipline, error-prone manual recording, and suboptimal digitalization of the administrative system. Solutions implemented include strengthening communication, providing internal training, implementing a fingerprint attendance system, and planning the development of an internal payment application. The implications of this study suggest that transformational leadership at the administrative level can serve as a model for school administrative management, one that is adaptable to technological developments, encourages staff professionalism, and fosters transparent and accountable educational governance in the digital era.